Training to Utilize Word of Mouth and Brand Image to Enhance Purchasing Decisions - Harahap, Isnaini; Novaliani Agustin, Dwi; Maisya Chairunysa, Fadia (Taqaddum: Community Service Journal, 2023)
Beauty products play a significant role in the lives of consumers, particularly for Generation Z, and have become a primary need in Indonesia, especially among women. The rapid growth of the beauty industry in Indonesia, coupled with increasing exports in the cosmetic market, underscores its importance. Effective marketing strategies, particularly word of mouth (WOM) and brand image, are crucial in influencing consumer attitudes and purchase decisions. This community service project utilized Focus Group Discussions (FGD) and collaboration methods to evaluate Somethinc’s marketing strategies. Results from the FGDs and subsequent training indicated that Somethinc had not fully implemented effective marketing strategies, leading to limited brand recognition. The project highlighted that effective marketing strategies could expand market reach, build consumer loyalty, and support sustainable growth. Maintaining a strong and consistent brand image is essential for creating long-term consumer relationships and competing effectively in the digital age. Somethinc’s use of social media platforms and engaging content, alongside loyalty programs and consistent branding, proved effective in retaining customers and enhancing brand awareness. This community service underscores the importance of understanding and applying effective marketing strategies to strengthen brand image and consumer loyalty in a competitive market.